2010
DOI: 10.1007/s10712-010-9108-9
|View full text |Cite
|
Sign up to set email alerts
|

On the P and S Receiver Functions Used for Inverting the One-Dimensional Upper Mantle Shear-Wave Velocities

Abstract: The teleseismic P receiver functions are customarily inverted to attain the seismic velocities beneath a seismic station. Surface wave dispersion data are often added to reduce the effect of the non-uniqueness. The combination of P receiver function and surface wave works well in resolving the structures in the crust and uppermost mantle, but is less effective in characterizing greater (lithosphere and asthenosphere) depths due to the interference from crustal multiples. A solution to this problem is jointly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 79 publications
0
7
0
1
Order By: Relevance
“…The earthquake data set was taken from the catalogue of the General Directorate Saunders et al (1998) 38 P and S-wave receiver function Çakır and Erduran (2011) 31-38 Receiver functions Tezel et al (2013) 25-40 S-receiver function Kind et al (2015) 37…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earthquake data set was taken from the catalogue of the General Directorate Saunders et al (1998) 38 P and S-wave receiver function Çakır and Erduran (2011) 31-38 Receiver functions Tezel et al (2013) 25-40 S-receiver function Kind et al (2015) 37…”
Section: Discussionmentioning
confidence: 99%
“…Tezel et al (2013) determined the crustal thickness in the central Anatolia to be 31-38 km determined by receiver function. Although Saunders et al (1998) and Çakır and Erduran (2011) found it to be about 38 km beneath central Anatolia, Kind et al (2015) determined the Moho depths to vary between 25 and 40 km by receiver function. Ateş et al (1999) analyzed the gravity and aeromagnetic anomalies of Turkey and showed that central Anatolia reflected relatively high-amplitude magnetic anomalies and intense negative gravity anomalies.…”
Section: Introductionmentioning
confidence: 96%
“…Reid et al () estimate lithospheric thicknesses of ∼60 km beneath Central Anatolia based on analysis of basaltic geochemistry. Estimates based upon receiver function analyses range between 60 and 90 km (Angus et al, ; Çakir & Erduran, ; Kind et al, ). A reasonable upper bound for present‐day lithospheric thickness is ∼120 km since a greater thickness would manifest itself as a substantial lithospheric root that should be visible in surface wave tomographic models (Priestley & McKenzie, ).…”
Section: Crustal and Lithospheric Templatesmentioning
confidence: 99%
“…A significant consideration is the relationship between present-day elevation and crustal thickness. Here, we have assembled a database of crustal thickness estimates derived from published receiver function analyses (Figure 2; supporting information Data Set S1; C¸akir & Erduran, 2004& Erduran, , 2011Erduran, 2009;G€ ok et al, 2008;Saunders et al, 1998;Taghizadeh-Farahmand et al, 2010;Tezel et al, 2010Tezel et al, , 2013Vanacore et al, 2013;van der Meijde et al, 2009;Zhu et al, 2006;Zor et al, 2003;2006). These analyses use the recorded travel times and amplitudes of direct and converted phases from teleseismic earthquakes to constrain the shear wave velocity structure of the crust and upper mantle.…”
Section: Receiver Function Analysesmentioning
confidence: 99%
“…They also found that P n velocities in the Eastern and Western Pontides are slower than in the Central Pontides. In addition, there are a number of crustal models from receiver function studies by Saunders et al (1998), Tok et al (2008) and Çakır & Erduran (2011) for the Anatolian region to name a few among others.…”
Section: Introductionmentioning
confidence: 99%